A History of Corporate Social Responsibility in Ghana - Amo-Mensah, Mavis (Advances in Social Sciences Research Journal, 2022)
There have been several contributions and research perspectives on Corporate Social Responsibility (CSR), however, research suggests that there is paucity of literature on historical accounts on the concept. There is also considerable evidence that the few CSR histories that have been documented have mostly focused on US-based literature. This paper attempts to detail the history of CSR in the Ghanaian context. The paper is a culmination of archival data and academic reviews on the history of CSR as well as interviews conducted with purposely selected informants. An analysis of the historical data revealed three key phases of CSR development in Ghana: the Pre-CSR phase, the Early CSR beginnings phase and the CSR Professionalisation phase. Significantly, this paper contributes to the prevailing CSR management literature, especially on national CSR histories. A thorough review of the literature suggests that there is no documented history on CSR in Ghana. This paper therefore addresses this gap. It contributes to a more distinctive historical understanding of how CSR has evolved from its early days to its current state in Ghana. It further provides useful background context to inform future research, analysis and interpretation.